LTE Optimization Using The Electrical Tilt Method At The Mandau Site - Mulyono; Mhd Azwar Taruna; Rika Susanti; Sutoyo Sutoyo (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Long Term Evolution (LTE) has high-speed data access of 300 Mbps on the downlink and 75 Mbps on the uplink. The area of ??the Mandau site is located in the town of Duri-Bengkalis, Riau. In this study, a network optimization was carried out on one of the providers. From the results of the drive test conducted, a problem was found, namely throughput quality which was in very bad condition. Therefore, a network optimization simulation was carried out using the Electrical Tilt method in order to overcome the problem of unstable throughput conditions. Simulation of the application of this method is carried out using Software Atoll. The results obtained after optimization with the value on Jalan Obor 2 increased to 19,000 kbps (normal), on Jalan Obor 1 increased to 50,000 kbps (very good), on Jalan Bandes increased to 50,000 kbps (very good), on Jalan Swadaya increased to 50,000 kbps (very good) and on Jalan Hangtuah increased to 50,000 kbps (very good).